Impact of Clinical Pharmacist-Vancomycin Monitoring on Patient Safety Outcome - Al-Ruwaisan, Rana; BaHmaid, Reem; Al-Banyan, Nora (Archives of Clinical and Biomedical Research, 2020)
Introduction: Vancomycin is frequently used to treat gram-positive infections especially methicillin- resistant Staphylococcus aureus (MRSA). Vancomycin level in the blood should be kept in a specific range to give the optimal antimicrobial killing and avoid the development of resistant and nephrotoxicity with low or high serum levels, respectively. This is known as "Therapeutic Drug Monitoring (TDM)." We aimed to evaluate the safety consequence of clinical pharmacist- based vancomycin TDM versus physician-based vancomycin TDM. Methods: Our study is a retrospective cohort study conducted at a single tertiary hospital, King Fahad Medical City (KFMC), Riyadh, Saudi Arabia. It included two groups one for physicians and one for clinical pharmacists. The patients were all adults more than 18 years old started on vancomycin intravenously for more than 24 hours for suspected or proven infection. The primary outcome was the development of nephrotoxicity. In addition to several secondary outcomes, that include appropriate vancomycin initial dosing, sampling time, interpretation of vancomycin level, and the development of other adverse reactions related to the use of vancomycin. Results: A total of 100 patients were enrolled in the study with 53 patients in the physician group. There were no significant differences in baseline characteristics between the two groups. The defined endpoint was reported as 3.8% (n=2) in physician group and 12.8% (n=6) in Clinical pharmacist group with a P value of 0.143. Moreover, there was a significant difference in the defined secondary endpoints that include appropriate vancomycin initial dosing, sampling time, interpretation of vancomycin level, and other adverse reactions with a P value of less than 0.001. Conclusion: There is a non-statistically significant higher rate of nephrotoxicity in